Radiosynthesis, Preclinical, and Clinical Positron Emission Tomography Studies of Carbon-11 Labeled Endogenous and Natural Exogenous Compounds - Shegani, Antonio; Kealey, Steven; Luzi, Federico; Basagni, Filippo; Machado, Joana do Mar; Ekici, Sevban Doğan; Ferocino, Alessandra; Gee, Antony D.; Bongarzone, Salvatore (Chemical reviews, 2023)
The presence of positron emission tomography (PET) centers at most major hospitals worldwide, along with the improvement of PET scanner sensitivity and the introduction of total body PET systems, has increased the interest in the PET tracer development using the short-lived radionuclides carbon-11. In the last few decades, methodological improvements and fully automated modules have allowed the development of carbon-11 tracers for clinical use. Radiolabeling natural compounds with carbon-11 by substituting one of the backbone carbons with the radionuclide has provided important information on the biochemistry of the authentic compounds and increased the understanding of their in vivo behavior in healthy and diseased states. The number of endogenous and natural compounds essential for human life is staggering, ranging from simple alcohols to vitamins and peptides. This review collates all the carbon-11 radiolabeled endogenous and natural exogenous compounds synthesised to date, including essential information on their radiochemistry methodologies and preclinical and clinical studies in healthy subjects.